IMPLEMENTASI TATA KELOLA PEMERINTAHAN DAERAH BERBASIS DIGITALISASI TEKNOLOGI DI INDONESIA - Riswati Riswati (Jurnal Media Birokrasi, 2021)
The government is conducting a transformation of Local Governance, based on Digitalization of Technology, for that the author is interested in conducting a research entitled "Implementation of Local Government Governance Based on Digitalization of Technology". benefits for the implementation of Good Governance in Indonesia. The method used in this study is a qualitative method, with descriptive analysis, with data sources from secondary data and primary data. The results and conclusions, that the application of technology digitization has been carried out by several local governments, in its implementation. However, not everything can run well, this is due to the limited ability of Human Resources, the support of other facilities and infrastructure, especially the internet connection network, which is still weak, so that it interferes in its implementation. However, the enthusiasm to do so is very, very good, so that the benefits in public services are felt by many people. Kominfo RI's commitment to support by improving the internet network throughout Indonesia. During the COVID-19 pandemic, most of the regional OPD OPDs that are responsible for providing public services have carried out public services using technology digitization applications. And people feel the satisfaction. Keywords: Implementation of Local Governance, Digitalization Based.